2016
DOI: 10.18632/oncotarget.11726
|View full text |Cite
|
Sign up to set email alerts
|

A three-gene signature for prognosis in patients with MGMT promoter-methylated glioblastoma

Abstract: Glioblastoma is the most malignant tumor and has high mortality rate. The methylated prompter of MGMT results in chemotherapy sensitivity for these patients. However, there are still other factors that affected the prognosis for the glioblastoma patients with similar MGMT methylation status. We developed a signature with three genes screened from the whole genome mRNA expression profile from Chinese Glioma Genome Atlas (CGGA) and RNAseq data from The Cancer Genome Atlas (TCGA). Patients with MGMT methylation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 28 publications
1
24
2
1
Order By: Relevance
“…Interestingly, they have emerged as prominent genes in glioblastoma: i) IKBIP has been described as a novel p53 target with pro-apoptotic activity, whose high expression is associated with poor prognosis in GBM (Cao et al 2019;Long and Li 2019) . Although in our results MGMT methylation was not considered a significant co-variable, another study has identified gene IKBIP as part of a signature that predicts prognosis only in GBM patients with methylated MGMT promoter (Wang et al 2016) . OSMR, characterized as a novel key regulator of glioblastoma tumorigenesis through EGFRvIII-STAT3 signaling, also correlates with poor prognosis in GBM patients both independently and also as part of a 4-gene signature (Mohan et al 2017;Cao et al 2019) .…”
Section: Discussioncontrasting
confidence: 76%
“…Interestingly, they have emerged as prominent genes in glioblastoma: i) IKBIP has been described as a novel p53 target with pro-apoptotic activity, whose high expression is associated with poor prognosis in GBM (Cao et al 2019;Long and Li 2019) . Although in our results MGMT methylation was not considered a significant co-variable, another study has identified gene IKBIP as part of a signature that predicts prognosis only in GBM patients with methylated MGMT promoter (Wang et al 2016) . OSMR, characterized as a novel key regulator of glioblastoma tumorigenesis through EGFRvIII-STAT3 signaling, also correlates with poor prognosis in GBM patients both independently and also as part of a 4-gene signature (Mohan et al 2017;Cao et al 2019) .…”
Section: Discussioncontrasting
confidence: 76%
“…The risk score was developed as previously reported [1719, 37], based on a linear combination of the lncRNA expression level (expr) weighted by the regression coefficient (β) derived from the univariate Cox regression analysis. The risk score for each patient was calculated as follows:…”
Section: Methodsmentioning
confidence: 99%
“…The top 10 screened candidate genes, listed by p-value, were considered as the preliminary range for risk score calculation. Based on the β and expression values of genes, the risk score for each sample was calculated by the following equation [15]:…”
Section: Risk Model Construction and Validationmentioning
confidence: 99%